Challenges, opportunities and sustainability of community forest associations and water resource users associations: A case of Kilungu catchment, Kenya (Journal of Sustainability, Environment and Peace, 2021)
Catchment degradation in the Kilungu catchment area in Kenya has persisted, albeit the presence of Kenze Community Forest Associations (CFAs) and Upper Kaiti Water Resources Users Associations (WRUAs) involvement. This study sought to assess the challenges faced by CFAs and WRUAs, available opportunities and sustainability in the management of the catchment, employing an exploratory, descriptive survey. Data was collected through household questionnaires, Focus Group Discussions (FGD), Key Informants’ Interviews (KII) and direct observations. The study established that Kenze CFA was facing major challenges at a rating of Very high (58%) and Highly (42%) as compared to Upper Kaiti WRUA at Very High (21%) and Highly (49), respectively. The Major challenges for the CFA being a non-functional CFA structure, while WRUAs challenges were minor on soft skills. Further, the challenges impacted highly on the outcomes of the CFA performance at a Very High (58%), Highly (42%) and WRUA Very High (21%) and Highly (49%), resulting in increased degradation of the catchment. In terms of opportunities, both institutions had various opportunities, although the WRUA had more opportunities at an affirmative Yes (99%) compared to CFA’s (54%). The key WRUA opportunity was that of being capacity build and empowered in order to ensure continuous efficient decision making and participatory management of the catchment, while the CFA had a supportive policy and law which presented a great opportunity of being enforced. Further, the WRUA respondents were more positive that the opportunities could improve the catchment at 38% (moderately), 42% (highly) and 20% (very high) compared to CFA’s 30% (moderately), 23% (highly) and 22% (very high). Results on Upper Kaiti WRUA and Kenze CFA respondent’s perceptions on sustainability revealed that both the WRUA and CFA were functioning well on aspects of equity and inclusiveness at WRUA rating of very highly (55 %), moderately (88%), and CFA very highly (25%), and moderately (50%). On accountability, WRUA had a rating of very highly (34%) and Moderate (88%), while the CFA was rated very highly (52%), and moderately (50%). In terms of WRUA and CFA effectiveness and efficiency, WRUA was rated very highly (36%), moderately (24) and CFA very highly (51%) and moderately (53%), respectively. Further results indicated that the WRUA highly involved its members in participatory decision making at moderately (88%) and highly (48%), compared to CFAs, who were rated at zero percent in the involvement of members in participatory decision making. On the observance of the rule of law, the WRUA were further rated highly (46%) and moderately (97%), while the CFAs were rated at zero percent. On consensus orientation, WRUAs were again rated highly (56%) and moderately (97%), while the CFAs were rated at zero percent. The study found that CFAs were facing more challenges, had fewer opportunities and various sustainability issues than the WRUAs, who were found to be having fewer challenges, had many opportunities and were significantly sustainable in all sustainability indicators. The implication of these results is that there is a critical need of addressing the challenges facing CFA and continually improve on the WRUA sustainability aspects as well as ensuring continuous empowerment of both institutions in order to overcome their myriad challenges, exploit their opportunities and ensure their sustainability. Further, there is a desperate need for a new and effective system for integrated Kilungu catchment management.
Keywords: Community Forest Association; Water Resources Users Association; Challenges; Opportunities; Sustainability; Kilungu catchment